ROLE OF CORPORATE SOCIAL RESPONSIBILITY (CSR) IN UPLIFTING DEFENCE SECTOR IN INDIA - Dr. Rahul Tripathi , Dr. G S Rajpal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Corporate social obligation has been a near illustration of beating difficulty in financing endless social upliftment programs, as a Nation building experience. Public security from both inside and outside perils calls for updating the social assurances of everybody. The test, thusly, lies in gathering the National security objections through enrollment and inciting of native assurance advances and stuff through Corporate Professional Responsibility programs as a subset or synchronous with Corporate Social Responsibility. Various areas are covered under CSR, however, the Defence Sector is still to be supported a lot. The paper intends to highlight the percentage and contribution of CSR in Defence sector of India.